PENGARUH KEPEMILIKAN MANAJERIAL, RASIO KEUANGAN DAN PENGUNGKAPAN CSR TERHADAP NILAI PERUSAHAAN - YOHANA CAHYANTI; Umar Issa Zubaidi (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to provide empirical evidence regarding the effect of the variables managerial ownership (MO), profitability (ROE), firm size (FS), corporate social responsibility (CSR), dividend payout ratio (DPR), leverage (DAR), cash holdings (CH) and current ratio (CR) to firm value (Tobin's Q) as the dependent variable. This research used data from non-financial companies that listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample data used in this research were 186 data (62 companies) which were selected using the purposive sampling method. The testing of secondary data in this research was testing through IBM SPSS 25 and research data were analyzed using multiple regression analysis method.The results of the research indicate the variables of profitability, corporate social responsibility, and leverage have an effect on firm value. Meanwhile, the variables of managerial ownership, firm size, dividend payout ratio, cash holdings and current ratio have no effect on firm value.